Double trouble: myocardial infarction with non-obstructive coronary arteries as a presentation of Hughes syndrome in monozygotic twins. (April 2020) - Djokovic, A; Stojanovich, L; Stanisavljevic, N; Popovic, M; Zdravkovic, M
Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a recently described, clinically significant entity, with prevalence rates ranging from 1% to 14% and a mean of 6% of all patients with myocardial infarction. Antiphospholipid syndrome (APS; Hughes syndrome) is characterized by the presence of antiphospholipid antibodies associated with thrombosis (arterial and/or venous) and/or pregnancy morbidity and could be the cause of MINOCA. Data on genetic predisposition to APS are scarce. The present study describes a unique case of monozygotic twin brothers who, at a young age, developed the same clinical presentation of APS. The diagnosis of APS was later confirmed, along with a diagnosis of systemic lupus erythematosus in one brother.